A prática de leitura no ensino de química: uma proposta pedagógica de ensino contextualizado - Girão, Luciene Nobre (2011)
The teaching of Chemistry aims to contribute with the citizenship formation as its contents are related to the environment, health and to a better quality of life. The students become aware of what is better for them and for the society. Reading is a very important skill for the teaching of sciences, mainly for the teaching of Chemistry. One of the objectives of this science teaching is to make students conscious of their role to transform the reality and the place where they live, however it is still recurrent the memorization of formulas as a tool for the teaching of Chemistry. This happens due to a depreciation of reading as fundamental tool for the teaching of any science. This work aims to analyze if the use of printed texts in the teaching of Chemistry influences reading and the comprehension of new scientific concepts. With this purposes we did a research in a public school in Fortaleza, Ce. The school works with students in the primary and secondary levels. Thirty students of 2nd grade participated in our research. They belonged to two different groups, group B with 17 students and group C with 13 students. The students participated in workshops in which they had to read texts on Acids, then they responded a questionnaire and wrote observations in the research’s diary. Most of the participants liked the workshops. The results show that 52,94% of B an 38,46% of C present better learning, though 23,53% of B and 23,08% of C, scored the same grade, and 23,53% of B and 38,46% of C lowered their grades. By comparing the data it is possible to see that there have been a little improvement in the students’ knowledge on the subject if we consider the whole group. On the other hand it is necessary to investigate what happened to the students that presented unsatisfactory or no improvement. At the end of this work we can consider that the work of a Chemistry teacher needs to be planned, re-planned, learned and relearned, evaluated and reevaluated as a common practice of the teacher himself/herself. The use of contextualized texts must be part of the teaching strategies, although their uses are not enough to guarantee successful learning.